Sonographic Diagnosis and Follow-Up of a Rare Large Pre-Patellar Morel-Lavallée Lesion - Peter Kam-To Siu; Wei-Ting Wu; Levent Özçakar; Ke-Vin Chang (Diagnostics)
Morel-Lavallée lesions (MLLs) in the knee are rare. This article presents one of the largest documented cases (13.46 × 12.73 × 3.03 cm), successfully managed non-operatively with clinical and sonographic follow-up. The patient was a 19-year-old male who sustained a bike accident, presenting with immediate gross swelling over the anterior knee, along with bruising and skin abrasions. He was unable to walk and was admitted to the orthopedic ward. A bedside handheld ultrasound examination revealed a large pre-patellar MLL, primarily filled with blood clots. Ultrasound-guided aspiration resulted in a dry tap. The diagnosis was confirmed through magnetic resonance imaging, and conservative management was implemented. At four weeks post-injury, the patient showed significant improvement. He achieved full range of knee motion seven weeks post-injury. Ultrasound imaging revealed a significantly reduced lesion size, with a sub-centimeter thickness. This case highlights the pivotal role of portable ultrasound in the acute diagnosis and follow-up of MLLs. It also demonstrates that, even with a lesion of substantial size, non-operative treatment can be highly effective. These findings provide valuable insights for developing treatment protocols for this rare condition.